Thirty-five Day Fluoxetine Treatment Limits Sensory-Motor Deficit and Biochemical Disorders in a Rat Model of Decompression Sickness - Cosnard, Caroline; De Maistre, Sébastien; Abraini, Jacques H.; Chazalviel, Laurent; Blatteau, Jean-Eric; Risso, Jean-Jacques; Vallée, Nicolas (Frontiers in Physiology, 2017)
According to the OECD statistical base for 2014, antidepressants will, on average, be distributed at a rate of 62 daily doses per 1000 inhabitants for the 25 countries surveyed (Health at a glance: Europe 2014; OECD Health Statistics). Divers must be concerned. On another hand, divers are potentially exposed to decompression sickness including coagulation inflammation and ischaemia, which can result in neurological lesions or even death. The purpose of this study is to assess whether chronic treatment with antidepressants may represent a contraindication to the practice of an at-risk activity, such as scuba diving, or even presents a benefit by attenuating the severity of the symptoms. We study for the first time the effect of a 35-day fluoxetine treatment (20 mg/kg) on the occurrence of decompression sickness in laboratory rats (n=79). Following exposure to the hazardous protocol, there is a significant correlation between the type of treatment and the clinical status of the rats in favour of a better clinical prognosis for the rats treated with fluoxetine with a significantly higher number of No DCS status and a lower number of Severe DCS status in the Flux, compared to Controls. The treatment modifies the rat performances both significantly and favourably during the physical and behavioural tests, just like their biological and biochemical constants. After decompression, rats under treatment display lower sensory-motor deficit and lowers biochemical disorders. From a biological point of view, we conclude fluoxetine should not be seen as a contraindication for diving on the basis of anticipated increased physiological risk.